2009
DOI: 10.1038/onc.2009.304
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous SWI/SNF chromatin remodeling complexes promote expression of microphthalmia-associated transcription factor target genes in melanoma

Abstract: The microphthalmia-associated transcription factor (MITF) promotes melanocyte differentiation and cell cycle arrest. Paradoxically, MITF also promotes melanoma survival and proliferation, acting like a lineage survival oncogene. Thus, it is critically important to understand the mechanisms that regulate MITF activity in melanoma cells. SWI/SNF chromatin remodeling enzymes are multiprotein complexes composed of one of two related ATPases, BRG1 or BRM, and 9-12 associated factors (BAFs). We previously determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
158
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(159 citation statements)
references
References 52 publications
0
158
0
1
Order By: Relevance
“…In six of the eight cell lines, mutations were biallelic (Table 1). In SK-MEL-5, only one allele has been found mutated, but this cell line has previously been shown to lack SMARCA4 expression, suggesting complete loss of function (29). In HEC1A, only one allele was mutated, and this cell line has previously been shown to express the SMARCA4 protein (30).…”
Section: Resultsmentioning
confidence: 98%
“…In six of the eight cell lines, mutations were biallelic (Table 1). In SK-MEL-5, only one allele has been found mutated, but this cell line has previously been shown to lack SMARCA4 expression, suggesting complete loss of function (29). In HEC1A, only one allele was mutated, and this cell line has previously been shown to express the SMARCA4 protein (30).…”
Section: Resultsmentioning
confidence: 98%
“…These factors include the Y-box binding protein-1, CCAAT-binding transcription factor 2, activating transcription factor 4, zincfinger factor 143, the nuclear transcription factor-B, the microphthalmia-associated transcription factor, the forkhead transcription factor O, and mitochondrial transcription factor A (Torigoe et al, 2005;Lee et al, 2009;Lei and Quelle, 2009;Li et al, 2009;Keenen et al, 2010). Hirano et al (2010) reported that p300/CBP-associated factor (PCAF) was overexpressed in human prostate and epidermal cisplatin-resistant P/CDP6 and HeLa/CP4 cells.…”
Section: A Transcription Factors Play a Major Role In Cisplatin Resimentioning
confidence: 99%
“…It was also described that MITF recruits the SWI/SNF complex to the promoters of differentiation-related targets Tyrosinase and TRP1, but not to cell maintenance genes TBX2 and BCL2. 27,28 This mechanism is suggested to drive selective expression of MITF target genes. SWI/SNF complexes are ATP-dependent chromatinremodeling enzymes that alter the position of nucleosomes along the chromosome and, as a consequence, affect promoter accessibility to regulatory factors.…”
Section: Dual Roles Of Lineage Restricted Transcription Factorsmentioning
confidence: 99%